Initial and permanent university teacher training. The experience of Burgos University - Delgado Benito, Vanesa (Historia y Comunicación Social, 2014)
In this article, the evolution of training courses is presented that target initial and ongoing teacher training at Burgos University. The body responsible for training is the Institute of Educational Training and Innovation (IFIE), which has organized a series of training programmes, among which the implementation of a Strategic Teacher Training Plan may be highlighted that is oriented towards innovation and the improvement of teacher training to assist the full integration of teaching staff in the European Higher Education Area.